KAJIAN ANALISIS CADANGAN PANGAN STRATEGIS TINGKAT RUMAH TANGGA DI KOTA MEDAN - Abdina, Muhammad Fadly; Sitorus, Reyza Suwanto; Qamari, Muhammad Al; Cemda, Abdul Rahmad (Fakultas Pertanian, Universitas Janabadra, 2023)
Food is everything that is a human need, which can come from water and biological sources, either through processing or not (direct consumption). Food is a source of strength needed by humans as an effort to maintain life, either as a source of energy or health. The purpose of this study is to determine the strategy for providing strategic food reserves at the household level, especially in food insecure areas in the city of Medan. The methodology used in the implementation of this activity is a qualitative approach (qualitative method). Qualitative research is research that seeks to find theories derived from data. The results of this study indicate that the performance of food production. The agricultural potential in Medan City is spread over 10 sub-districts including Medan Tuntungan, Medan Johor, Medan Amplas, Medan Polonia, Medan Selayang, Medan Sunggal, Medan Helvetia, Medan Deli, Medan Labuhan, and Medan Marelan. Food reserves, especially rice for the city of Medan, still have to be imported from other regions/regions, because the amount of harvest in the city of Medan is very disproportionate to the population of the city of Medan. Keywords: food security, food availability, food accessibility, food production INTISARIPangan adalah segala sesuatu yang menjadi kebutuhan manusia, yang bisa saja berasal dari sumber air dan hayati, baik melalui proses pengolahan ataupun tidak (langsung dijadikan konsumsi). Pangan adalah sumber kekuatan yang dibutuhkan oleh manusia sebagai upaya mempertahankan kehidupan, baik sebagai sumber tenaga atau kesehatan. Tujuan dari penelitian ini Mengetahui strategi penyediaan cadangan pangan strategis tingkat rumah tangga terutama di daerah rawan pangan di kota medan. Metodelogi yang digunakan dalam pelaksanaan kegiatan ini adalah dengan pendekatan secara kualitatif (qualitative methode). Penelitian kualitatif merupakan penelitian yang berusaha menemukan teori yang berasal dari data. Hasil penelitian ini menunjukkan bahwa kinerja produksi pangan Potensi pertanian yang terdapat di Kota Medan tersebar pada 10 kecamatan diantaranya, Kecamatan Medan Tuntungan, Medan Johor, Medan Amplas, Medan Polonia, Medan Selayang, Medan Sunggal, Medan Helvetia, Medan Deli, Medan Labuhan, dan Medan Marelan. Cadangan pangan terutama beras kota Medan masih harus didatangkan dari daerah/wilayah lain, karena jumlah panen yang ada di kota Medan sangat tidak sebanding dengan jumlah penduduk kota Medan. Kata kunci: ketahanan pangan, ketersediaan pangan, aksesibilitas pangan, produksi pangan